SEPTOPLASTY BY USING SEPTAL CLIP TO AVOID NASAL OBSTRUCTION DUE TO NASAL TAMPONADE AFTER SEPTAL SURGERY - Siti Masliana Siregar (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
AbstractSeptal deviation are pretty common occurence and eventhough septal deviations are common they are usually not severe enough to cause symptoms.1 The deviated nose is a common deformity encountered in rhinoplasty, and yet it remains one of the most difficult and challenging pathologies to treat, even for experienced surgeons.2 Although numerous surgical approaches have been documented in the literature, there is still no technique that can guarantee a succesfull outcome, and no technique has a clearly lower revision rate. To enable more accurate diagnosis and treatment of deviated nose, some studies have created criteria by which to categorize deviations.3,4 Nasal Packs are indispensable in ENT practice. Functional endoscopic endonasal sinus surgery allows the use of modern nasal packs, since pressure is no longer required. So called hemostatic/ resorbable materials are a first step in this direction. However, they may lead to adhesions and foreign body reactions in mucosal membranes.5 Nasal packing is routinely used after septoplasty because it is believed to decrease risk of postoperative bleeding, hematomas, and adhesions. Multiple studies have shown, however, that there are numerous complications associated with nasal packing. Nasal packing after septoplasty does not show any postoperative benefits. Fibrin products show a possibility of decreasing postoperative bleeding. Routine use of nasal packing after septoplasty is not warranted. 6Keywords: Septal Deviation, Septoplasty, Nasal Packing, Septal Clip